The Existence and Regulation of Cyber Law: The Government's Role in Combating Digital Crime in Indonesia - Auliaurrahman, Auliaurrahman; Anshari, Nur; Firdaus, Sunny Ummul (State of Islamic Institute Langsa, 2025)
Ideally, cyber law regulations in Indonesia should provide comprehensive protection against digital crime in line with the rapid development of information technology. However, in reality, the existing regulations still face various challenges in law enforcement and have not fully succeeded in reducing the increasing rate of digital crime. This study aims to analyze the existence and effectiveness of cyber law regulations in Indonesia and evaluate the role of the government in combating digital crime. This research employs a qualitative approach with a literature review method, involving descriptive analysis and a comparative study between Indonesian cyber regulations and international regulations. The findings indicate that although Indonesia has an adequate legal basis through the Electronic Information and Transactions Law (UU ITE), its implementation remains ineffective due to infrastructure limitations and lack of inter-agency coordination. Furthermore, a comparison with international regulations reveals the need for revision and policy strengthening to enhance national cybersecurity.